DNA methylation and transcriptomic changes in response to different lights and stresses in 7B-1 male-sterile tomato - Omidvar, Vahid; Fellner, Martin (PloS one, 2015)
We reported earlier that 7B-1 mutant in tomato (Solanum lycopersicum L., cv. Rutgers), an ABA overproducer, is defective in blue light (B) signaling leading to B-specific resistance to abiotic and biotic stresses. Using a methylation-sensitive amplified polymorphism (MSAP) assay, a number of genes were identified, which were differentially methylated between 7B-1 and its wild type (WT) seedlings in white (W), blue (B), red (R) lights and dark (D) or in response to exogenous ABA and mannitol-induced stresses. The genomic methylation level was almost similar in different lights between 7B-1 and WT seedlings, while significant differences were observed in response to stresses in D, but not B. Using a cDNA-AFLP assay, several transcripts were identified, which were differentially regulated between 7B-1 and WT by B or D or in response to stresses. Blue light receptors cryptochrome 1 and 2 (CRY1 and CRY2) and phototropin 1 and 2 (PHOT1 and PHOT2) were not affected by the 7B-1 mutation at the transcriptional level, instead the mutation had likely affected downstream components of the light signaling pathway. 5-azacytidine (5-azaC) induced DNA hypomethylation, inhibited stem elongation and differentially regulated the expression of a number of genes in 7B-1. In addition, it was shown that mir167 and mir390 were tightly linked to auxin signaling pathway in 5-azaC-treated 7B-1 seedlings via the regulation of auxin-response factor (ARF) transcripts. Our data showed that DNA methylation remodeling is an active epigenetic response to different lights and stresses in 7B-1 and WT, and highlighted the differences in epigenetic and transcriptional regulation of light and stress responses between 7B-1 and WT. Furthermore, it shed lights on the crosstalk between DNA hypomethylation and miRNA regulation of ARFs expression. This information could also be used as a benchmark for future studies of male-sterility in other crops.
Keywords: rostlinné proteiny; DNA Methylation; světlo; Solanum lycopersicum; mutace; Mutation; metylace DNA; neplodnost rostlin; Plant Infertility; Light; Plant Proteins; Transcription, Genetic; genetická transkripce